Keanekaragaman dan Komposisi Serangga pada Tanaman Jagung di Tojo Una-Una, Sulawesi Tengah, Indonesia - Muhammad Amiruddin; Nuranisa Nuranisa; Jeki Jeki; Rosida P. Adam; Diky Dwiyanto (Institut Pertanian Bogor, 2023)
Various insects (Arthropoda: Insecta) have an important role in the agricultural sector, including corn crops. Understanding the diversity of species and composition of insects in the plantation area is a necessary first step in implementing integrated pest management (IPM). This study aims to analyze the diversity of species and composition of insects found in corn plantation in the Malotong Village, Tojo Una-Una Regency, Central Sulawesi. Sampling was carried out in October and November 2022 using insect nets in four plots. A total of 21 species (16 families and four orders) were found in this study, with the order Hemiptera having the highest number of families and genus (7 families and 8 genera). The Shannon diversity index (H′) showed moderate criteria, with the highest found in plot 1 (H′=1,60), while the highest Evenness index values were found in plots 3 (0,77) and 4 (0,74). The highest similarity indexes were found in plots 2 and 3 (0,53), as a result of their shared vegetation patterns. The composition of insects consists of herbivores, predators, and pollinators, with the highest percentage being herbivores (68.5%), then predators (25%), and the lowest being pollinators (6.5%). Keywords: Abundance, Central Sulawesi, corn, IPM, Tojo Una-Una